The Leaf nutrient content of ‘Jade’ peach grafted on 22 clonal rootstock and in own-rooted trees - Mayer, Newton Alex; Navroski, Renan; Benati, Jorge Atílio; Roth, Fernanda Maísa; Ueno, Bernardo; Nava, Gilberto; Corrêa Antunes, Luis Eduardo; Valgas, Ricardo Alexandre (Comunicata Scientiae, 2023)
The objective of this research was to evaluate the effects of 22 clonal rootstocks and own-rooted scion trees (without rootstock) on leaf nutrient contents (N, P, K, Ca, Mg, Mn, Fe, Zn, Cu and B) of the ‘Jade’ scion peach growing in a no-irrigated area with Peach Tree Short Life (PTSL) history, as well as their effects on nutrient agronomic interpretation. Macronutrient (N, P, K, Ca and Mg) and micronutrient contents (B, Cu, Fe, Mn and Zn) were determined in the first and second years after tree planting, in Pelotas-RS, Brazil. We conclude that leaf contents of P, K, Ca, Mg, B, Cu, Mn and Zn are influenced by the scion/rootstock combinations and own-rooted trees tested. Treatments changed agronomic interpretation classes of all macro and micronutrients. For macronutrients, ‘Flordaguard’, De Guia, Tardio-01 rootstocks and the own-rooted trees stood out, with leaf nutrient contents similar or even higher than trees grafted on ‘Capdeboscq’ and ‘Aldrighi’. For micronutrients, trees on GxN.9, ‘Ishtara’ and ‘Santa Rosa’ plum stood out. From a nutritional point of view, own-rooted ‘Jade’ peach trees did not present any limitations.